2023
DOI: 10.1097/acm.0000000000005256
|View full text |Cite
|
Sign up to set email alerts
|

Residency Program Directors’ Views on Research Conducted During Medical School: A National Survey

Abstract: Purpose With the United States Medical Licensing Examination Step 1 transition to pass/fail in 2022, uncertainty exists regarding how other residency application components, including research conducted during medical school, will inform interview and ranking decisions. The authors explore program director (PD) views on medical student research, the importance of disseminating that work, and the translatable skill set of research participation. Method Surveys were distributed to all U.S. residency PDs and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…As part of our systematic review, we also examined a variety of other residency application factors that did not qualify for meta-analysis due to the lack of uniformity in data presentation among studies. These factors include core clerkship grades, 4,14,22,25-27,30,34,35,39,40,43,49 class rank, 4,14,25,34,40,43,49 MSPE/Dean’s Letter, 4,14,18,22,26,27,34,35,40,43,49 letters of recommendation, 4,14,22,26,27,30,31,34,35,39,40,43,49 research, 4,12,14,22,25-27,30,34,35,37,39,40,43,45,49,50 personal statement, 4...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our systematic review, we also examined a variety of other residency application factors that did not qualify for meta-analysis due to the lack of uniformity in data presentation among studies. These factors include core clerkship grades, 4,14,22,25-27,30,34,35,39,40,43,49 class rank, 4,14,25,34,40,43,49 MSPE/Dean’s Letter, 4,14,18,22,26,27,34,35,40,43,49 letters of recommendation, 4,14,22,26,27,30,31,34,35,39,40,43,49 research, 4,12,14,22,25-27,30,34,35,37,39,40,43,45,49,50 personal statement, 4...…”
Section: Resultsmentioning
confidence: 99%
“…After the initial search, 351 duplicates were removed and 44 were excluded after title and abstract review, 4,[7][8][9][10][11][12][13][14][15] based on inclusion and exclusion criteria. [16][17][18][19][20][21][22][23][24][25] Full-text review was performed on 98 articles, [26][27][28][29][30][31][32][33][34][35] of which 45 studies were included [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (see Figure, Supplemental Digital Content 5, which illustrates a flow-chart of our literature search, as well as our full search strategies).…”
Section: Study Selectionmentioning
confidence: 99%
“…Since the US Medical Licensing Examination (USMLE) Step 1 transitioned to pass/fail in 2022, there is an even greater pressure on medical students to differentiate themselves on their residency applications. A recent survey of US residency programme directors found that they value meaningful engagement and completion of research as it demonstrates desirable attributes such as critical thinking, time management and self‐directed learning 1 . The study also found that research in medical education was in the top three categories reported as high value behind clinical research and quality improvement.…”
Section: What Problem Was Addressed?mentioning
confidence: 91%
“…One such experience that is growing in importance is research. 9 Many students participate in research during their preclinical years to get a head-start on that aspect of the residency application. 8 Research in pathology is an effective way to get students into the pathology department while still being able to tie their work to different specialty interests.…”
Section: The Preclinical Yearsmentioning
confidence: 99%